The Influence of Financial Literacy, Self-Control, and Lifestyle on Universitas Tarumanagara Students’ Interest in Saving - Putri Janice Liliana Sutarman; Joyce A. Turangan (International Journal of Application on Economics and Business, 2023)
This study aims to determine the prediction of the influence of financial literacy, self-control, and lifestyle on Universitas Tarumanagara students’ interest in saving. The research sample was 50 students. This research method uses SmartPLS and by distributing questionnaires via Google Form. The results of this study are that there is a positive and significant influence of financial literacy, a negative and not significant influence of self-control, and a positive but not significant influence of lifestyle on Universitas Tarumanagara students’ interest in saving.